Congenital Cytomegalovirus Infection Burden and Epidemiologic Risk Factors in Countries With Universal Screening - Paddy Ssentongo; Christine Hehnly; Patricia Birungi; Mikayla A. Roach; Jada Spady; Claudio Fronterrè; Ming Wang; Laura E. Murray‐Kolb; Laila Al‐Shaar; Vernon M. Chinchilli; James R. Broach; Jessica E. Ericson; et al. (2021)
Importance Congenital cytomegalovirus (cCMV) infection is the most common congenital infection and the leading acquired cause of developmental disabilities and sensorineural deafness, yet a reliable assessment of the infection burden is lacking. Objectives To estimate the birth prevalence of cCMV in low- and middle-income countries (LMICs) and high-income countries (HICs), characterize the rate by screening methods, and delineate associated risk factors of the infection. Data Sources MEDLINE/PubMed, Scopus, and Cochrane Database of Systematic Reviews databases were searched from January 1, 1960, to March 1, 2021, and a total of 1322 studies were identified. Study Selection Studies that provided data on the prevalence of cCMV derived from universal screening of infants younger than 3 weeks were included. Targeted screening studies were excluded. Data Extraction and Synthesis Preferred Reporting Items for Systematic Reviews and Meta-analyses guideline was followed. Extraction was performed independently by 3 reviewers. Quality was assessed using the Newcastle-Ottawa Scale for cohort studies. Random-effects meta-analysis was undertaken. Metaregression was conducted to evaluate the association of sociodemographic characteristics, maternal seroprevalence, population-level HIV prevalence, and screening methods with the prevalence of cCMV. Main Outcomes and Measures Birth prevalence of cCMV ascertained through universal screening of infants younger than 3 weeks for CMV from urine, saliva, or blood samples. Results Seventy-seven studies comprising 515 646 infants met the inclusion criteria from countries representative of each World Bank income level. The estimated pooled overall prevalence of cCMV was 0.67% (95% CI, 0.54%-0.83%). The pooled birth prevalence of cCMV was 3-fold greater in LMICs (1.42%; 95% CI, 0.97%-2.08%; n = 23 studies) than in HICs (0.48%; 95% CI, 0.40%-0.59%, n = 54 studies). Screening methods with blood samples demonstrated lower rates of cCMV than urine or saliva samples (odds ratio [OR], 0.38; 95% CI, 0.23-0.66). Higher maternal CMV seroprevalence (OR, 1.19; 95% CI, 1.11-1.28), higher population-level HIV prevalence (OR, 1.22; 95% CI, 1.05-1.40), lower socioeconomic status (OR, 3.03; 95% CI, 2.05-4.47), and younger mean maternal age (OR, 0.85; 95% CI, 0.78-0.92, older age was associated with lower rates) were associated with higher rates of cCMV. Conclusions and Relevance In this meta-analysis, LMICs appeared to incur the most significant infection burden. Lower rates of cCMV were reported by studies using only blood or serum as a screening method.